Effect of Mg and Ca on the Stability of the MRI Contrast Agent Gd–DTPA in Seawater - Schijf, Johan; Christy, Isabel J. (Frontiers in Marine Science, 2018)
Gadolinium diethylenetriaminepentaacetic acid (Gd–DTPA) is widely applied as a contrast enhancer in medical MRI. As Gd–DTPA is only minimally captured in wastewater treatment plants (WTPs) or degraded by UV light and other oxidative processes, concentrations in rivers have increased globally by orders of magnitude following its introduction in 1987. The complex also seems impervious to estuarine scavenging and is beginning to emerge in coastal waters, yet it is unknown how its stability is changed by competition for the DTPA ligand from major seawater cations. We performed potentiometric titrations at seawater ionic strength (0.7 M NaClO4) to determine dissociation constants of the five DTPA carboxylic acid groups, as well as stability constants of Mg, Ca, and Gd complexes with the fully deprotonated and single-protonated ligand. These are in general agreement with literature values at low ionic strength and confirm that complexes with Ca are more stable than with Mg. A new finding, that the DTPA complexes of Mg and Ca appear to be hydrolyzed at elevated pH, implies that their coordination in these chelates is less than hexadentate, enabling additional competition with Gd from dinuclear Mg and Ca species. Side-reaction coefficients for trace-metal-free seawater, calculated from our results, suggest that the higher abundance of Mg and Ca may significantly destabilize Gd–DTPA in coastal waters, causing dissociation and release of as much as 15% of the organically complexed Gd from the ligand. This effect could enhance the particle-reactivity and bioavailability of anthropogenic Gd in sensitive estuarine habitats, indicating an urgent need to further study the fate of this contaminant in marine environments.